Recruitment of Older Kidney Transplant Recipients to a Longitudinal Study. Issue 3 (May 2020) - O'Brien, Tara; Russell, Cynthia L.; AlKahlout, Noor; Rosenthal, Anna; Meyer, Tess; Tan, Alai; Daloul, Reem; Hathaway, Donna
Abstract : Background: Currently, limited information is available regarding selection of the most successful strategies for recruitment of older adult kidney transplant recipients as research participants. Objective: The aim of this study was to explore multiple modes of recruitment strategies to enroll older kidney transplant recipients in a 1-year longitudinal study. Methods: We used a feasibility design to explore the following recruitment methods: face-to-face contact in the transplant clinic, paper flyers placed in the transplant clinic, Facebook, an online transplant newsletter, and a university website listing of research studies. Results: Enrollment was open for 9 months, during which time websites and the Facebook portal were active, 142 newsletters were e-mailed, and 424 patients were approached in the transplant clinic. Among patients approached in the clinic, 12 did not own a smartphone required for the study. The sample consisted of 60 participants (39 men, 21 women), with a mean age of 64.5 ± 4.7 years. Of the participants who enrolled in the study, the largest number (75%, n = 45) was recruited using the face-to-face method in the transplant clinic. The online transplant newsletter was the second-best recruitment source (18%, n = 11). Discussion: Recruitment strategies using face-to-face contact and the online newsletter associated with the transplant clinic organization appeared to be more effective than strategies not associated with the transplant clinic (Facebook and university website). Findings suggest that using a familiar organization communication method to recruit older chronic disease population may be the most beneficial.